Simultaneous EEG and fMRI reveals stronger sensitivity to orthographic strings in the left occipito-temporal cortex of typical versus poor beginning readers. (December 2019) - Pleisch, Georgette; Karipidis, Iliana I.; Brem, Alexandra; Röthlisberger, Martina; Roth, Alexander; Brandeis, Daniel; Walitza, Susanne; Brem, Silvia
Abstract: The level of reading skills in children and adults is reflected in the strength of preferential neural activation to print. Such preferential activation appears in the N1 event-related potential (ERP) over the occipitotemporal scalp after around 150–250 ms and the corresponding blood oxygen level dependent (BOLD) signal in the ventral occipitotemporal (vOT) cortex. Here, orthography-sensitive (print vs. false font) processing was examined using simultaneous EEG-fMRI in 38 first grade children with poor and typical reading skills, and at varying familial risk for developmental dyslexia. Coarse orthographic sensitivity was observed as an increased activation to print in the N1 ERP and in the BOLD signal of individually varying vOT regions in 57% of beginning readers. Finer differentiation in processing orthographic strings (words vs. nonwords) further occurred in specific vOT clusters. Neither method alone showed robust differences in orthography-sensitive processing between typical and poor reading children. Importantly, using single-trial N1 ERP-informed fMRI analysis, we found differential modulation of the orthography-sensitive BOLD response in the left vOT for typical readers only. This result, thus, confirms subtle functional alterations in a brain structure known to be critical for fluent reading at the very beginning of reading instruction.